Results from patient-derived xenograft models support co-administration of allopurinol and 6-mercaptopurine to reduce hepatotoxicity and improve event-free survival in pediatric acute lymphoblastic leukemia - Yixiao Mo; Qi Zhang; Miao Wang; Jihui Chen; Wenting Hu; Changcheng Chen; Yanjing Tang; Zhuo Wang; Jingjing Wang; Xiaoxiao Chen; Shuhong Shen (Haematologica)
Not available.